Molecular simulation on the influence of FeS2 on anthracite adsorption of CH4 and O2 - Dameng Gao; Xinyue Xu (Journal of Saudi Chemical Society)
In order to study the adsorption characteristics of gas and oxygen in coal seams containing ferrous disulfide, the molecular structure model of anthracite and the structural model of ferrous disulfide were constructed respectively, and the adsorption isotherms of ferrous disulfide crystal and anthracite for single component O2 and CH4 were calculated. Based on the experimental data of inorganic sulfur content in coal, the structural models of ferrous disulfide and anthracite were mixed in different proportions, and the structural models of anthracite with inorganic sulfur content of 1.17 %, 2.61 %, 0.75 % and 3.78 % were established, and the adsorption characteristics of O2 and CH4 were calculated and analyzed. The results show that the adsorption rate of single component O2 in FeS2 is higher than that of CH4, which is greatly influenced by pressure and temperature. The binding capacity of O2 with S is stronger than that with Fe, and CH4 is diagonally adsorbed in ferrous disulfide crystal. At 0 ∼ 1 MPa, the adsorption capacity of anthracite for CH4 is greater than that of O2; After 1 MPa, the adsorption rate and capacity of O2 were higher than that of CH4. With the increase of FeS2 content doped with anthracite, the adsorption capacity of CH4 and O2 decreased. When binary components O2 and CH4 are adsorbed on FeS2-doped anthracite, the larger the proportion of O2, the closer the sum of adsorption capacity of mixed gas is to that of single component gas.